Safeguarding Brands: Trademark Infringement Challenges in India's Food Industry (International Journal of Food and Nutritional Sciences, 2021)
This paper examines the prevalence and implications of trademark infringement within the food industry in India. With the rise of counterfeit products and brand imitation, businesses face significant challenges in protecting their intellectual property. The study highlights the legal framework established by the Trade Marks Act, 1999, which serves to safeguard trademarks and ensure consumer trust. Notable cases of trademark infringement are analyzed to illustrate the complexities of enforcement and the repercussions for both businesses and consumers. Additionally, the paper discusses effective strategies for prevention and enforcement, including the importance of trademark registration, the role of legal counsel, and collaborative efforts between businesses and regulatory bodies. Ultimately, this research underscores the need for robust trademark management practices to foster a competitive and trustworthy marketplace.